The Effects of Non-Audit Fees and Auditor Tenure on Audit Quality in the U.K - PANG, Wei (2017)
Due to several accounting scandals, regulators have raised concerns about the impacts of non-audit fees and auditor tenure on audit quality. This research intends to investigate whether auditor tenure and non-audit fees affect audit quality. This paper employs Jones (1991) model in a cross-sectional way to obtain unexpected accruals, and uses them as proxies for audit quality. On a basis of 785 U.K. observations in 2014 and 2015, the multivariate regression results indicate that auditor tenure and non-audit fees are insignificantly related to audit quality, indicating that longer auditor tenure and higher non-audit fees would not result in worse audit quality. Therefore, this study makes some contributions to the current issue about whether regulators should force firms to change their auditors mandatorily and has implications for relevant regulators in the U.K in regard to future improvements of audit quality.